Design of heterostructure photocatalysts based on layered perovskite-like bismuth silicate - Belik, Yulia A.; Vergilessov, Roman A.; Kovaleva, Evgenia A.; Svetlichnyi, Valerii A.; Vodyankina, Olga V. (Applied surface science)
Heterostructure photocatalysts attract a lot of attention of researchers thanks to their enhanced photocatalytic performance. Herein, we focus on the formation of the p-n type heterojunction based on bismuth metasilicate Bi2SiO5 and β-Bi2O3. To date, there are some publications dedicated to these objects, however, the monitoring of the phase composition in the Bi2O3-Bi2SiO5 system and strong evidence of the heterostructure formation in the composite material have not been provided together. At first, we show with quantum-chemical calculations that such interface is possible to design. After that, using XRD in situ we clearly show the pathway of formation of Bi2SiO5 by consuming β-Bi2O3 phase with increasing of temperature. Such results allow monitoring the phase content of the composite material. Finally, we choose two calcination modes to prepare the samples. Based on the results of HRTEM, DRS, XRD, IR and Raman data we clearly show the difference between the mechanical mixture of the semiconductors and generated heterostructure material. Photocatalytic properties of the samples are tested in photodegradation of Rhodamine B under different wavelength of LEDS. Under visible light (470 nm) the heterostructure demonstrates better catalytic activity. Additionally, using air flow and trapping agents it is demonstrated that the holes h+ mainly take part in deethylation of the dye.